2009
DOI: 10.1056/nejmoa0803267
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Elective Repeat Cesarean Delivery at Term and Neonatal Outcomes

Abstract: BACKGROUND Because of increased rates of respiratory complications, elective cesarean delivery is discouraged before 39 weeks of gestation unless there is evidence of fetal lung maturity. We assessed associations between elective cesarean delivery at term (37 weeks of gestation or longer) but before 39 weeks of gestation and neonatal outcomes. METHODS We studied a cohort of consecutive patients undergoing repeat cesarean sections performed at 19 centers of the Eunice Kennedy Shriver National Institute of Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
412
9
15

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 737 publications
(494 citation statements)
references
References 25 publications
42
412
9
15
Order By: Relevance
“…(i) The WHO criteria for the diagnosis of diabetes mellitus in pregnancy [307] and the WHO and the International Association of Diabetes in Pregnancy Study Group criteria for diagnosis of GDM [307,308] should be used when possible.…”
Section: Consensus Recommendationsmentioning
confidence: 99%
“…(i) The WHO criteria for the diagnosis of diabetes mellitus in pregnancy [307] and the WHO and the International Association of Diabetes in Pregnancy Study Group criteria for diagnosis of GDM [307,308] should be used when possible.…”
Section: Consensus Recommendationsmentioning
confidence: 99%
“…On these subgroups, vaginal delivery rate exceeded 90% on the first group and came close to it on the second. Even though the consequences of overestimation do not seem to be important when we look at the risk of cesarean section, it is important to keep in mind that this may imply inducing delivery on the early term period, which is not completely innocuous for the baby [10]. In G3, fetuses with overestimated fetal weight did also show lower tolerance to labor, with rates of vaginal delivery similar to the “true FGR” with pathological fetal Doppler study.…”
Section: Discussionmentioning
confidence: 99%
“…However, in other studies on 36-week-old infants with respiratory distress, it was suggested that cesarean section before the onset of labor might be beneficial (19,20). Therefore, based on the association between newborn respiratory problems and high frequency of cesarean section before the week 39, which result in newborn's hospitalization in NICU (21)(22)(23), to reduce TTN incidence in infants, it is recommended that obstetrician give full awareness to mothers about the risk Iran Red Crescent Med J. In Press(In Press):e56550.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%